Manajemen Kebencanaan pada Buku Bahasa Indonesia Kelas VII SMP - Sigit Arif Bowo (LP. Ma'arif Janggan Magetan, 2022)
ndonesia is a country that has the potential to be heavily affected by disasters. These disasters are caused by natural and non-natural factors. The number of victims and losses due to disasters requires a response for all communities. This study aims to describe the form of disaster management in Indonesian books at the junior high school level. The data source for this research is Indonesian class VII books published by the Center for Books and Curriculum of the Ministry of Education and Culture in 2021. The data in this study are words, sentences, paragraphs, and discourses in Class VII Indonesian Books related to forms of disaster management. Data collection techniques used listening, analysis, and note-taking techniques. The data analysis technique uses interactive analysis which consists of data reduction, data presentation, and drawing conclusions elaborated with relevant theories. The results of the analysis show that out of the six chapters, there are four chapters of disaster management materials in Indonesian class VII books. The material includes elements of disaster consisting of prevention (mitigation), preparation (preparedness), response (response), and repair (recovery). These materials are displayed in the form of readings and practice questions scattered in descriptive texts, explanations, news, stories, and letters.